2022
DOI: 10.9734/jpri/2022/v34i41b36274
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Kangaroo Mother Care among Low Birth Weight Newborns at a Tertiary Care Hospital: A Cross-Sectional Study

Abstract: Aim: To assess the efficacy of Kangaroo Mother Care (KMC) among low birth weight neonates at a tertiary care hospital Study Design: A cross-sectional study Place and Duration. The Kangaroo mother care ward, CMC Children Hospital, Larkana from August 2019 to February 2020. Methodology: Total 345 low birth weight patients were included. Newborns were kept in KMC position. Axillary temperature was measured during KMC position. Stratification of study variables was done while post-stratification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…15 Previous studies have reported that KC also decreases the length of hospitalization. [16][17][18][19][20] The survival of premature infants has improved due to the application of KC as a cost-effective and high-quality treatment. 21 It was initially considered an accepted practice appropriate for resource-limited settings rather than a global standard of care.…”
Section: Introductionmentioning
confidence: 99%
“…15 Previous studies have reported that KC also decreases the length of hospitalization. [16][17][18][19][20] The survival of premature infants has improved due to the application of KC as a cost-effective and high-quality treatment. 21 It was initially considered an accepted practice appropriate for resource-limited settings rather than a global standard of care.…”
Section: Introductionmentioning
confidence: 99%